2021
DOI: 10.1002/adma.202100340
|View full text |Cite
|
Sign up to set email alerts
|

A Floating Mold Technique for the Programmed Assembly of Protocells into Protocellular Materials Capable of Non‐Equilibrium Biochemical Sensing

Abstract: Despite important breakthroughs in bottom‐up synthetic biology, a major challenge still remains the construction of free‐standing, macroscopic, and robust materials from protocell building blocks that are stable in water and capable of emergent behaviors. Herein, a new floating mold technique for the fabrication of millimeter‐ to centimeter‐sized protocellular materials (PCMs) of any shape that overcomes most of the current challenges in prototissue engineering is reported. Significantly, this technique also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Other than protein pore-mediated direct signaling, there are few examples where proteinosomes have been cross-linked using covalent bonds to form synthetic tissues exhibiting internal signaling ( Figure 2B ). Gobbo et al used covalent biorthogonal chemistry to crosslink proteinosomes to construct artificial prototissues ( Gobbo et al, 2018 ) and recently showed direct signal exchange between covalently crosslinked GOx and HRP-loaded artificial cells to produce resorufin as final product ( Galanti et al, 2021 ). In this case, the high molecular cut-off of the proteinosome membrane allows fast internal signaling within the synthetic tissues.…”
Section: Distance-based Classification Of Artificial Cell Communicationmentioning
confidence: 99%
“…Other than protein pore-mediated direct signaling, there are few examples where proteinosomes have been cross-linked using covalent bonds to form synthetic tissues exhibiting internal signaling ( Figure 2B ). Gobbo et al used covalent biorthogonal chemistry to crosslink proteinosomes to construct artificial prototissues ( Gobbo et al, 2018 ) and recently showed direct signal exchange between covalently crosslinked GOx and HRP-loaded artificial cells to produce resorufin as final product ( Galanti et al, 2021 ). In this case, the high molecular cut-off of the proteinosome membrane allows fast internal signaling within the synthetic tissues.…”
Section: Distance-based Classification Of Artificial Cell Communicationmentioning
confidence: 99%
“…In addition to micelles, vesicles can be incorporated into hydrogels as well (Figure 2d,e), e.g., liposomes based on lipids, [100,101] niosomes based on nonionic surfactants, [102,103] vesicles from cellular origin, [104] vesicles based on ionic surfactants, [105][106][107] proteinosomes based on protein-polymer conjugates [108,109] or polymersomes based on block copolymers. [110] A feature of vesicular structures is the membrane that separates the interior aqueous medium from the exterior aqueous medium, which contains a hydrophobic barrier.…”
Section: Vesiclesmentioning
confidence: 99%
“…(E) Schematic of chemical communication based on a GOx/HRP enzyme cascade reaction within a protocellular material. Details on the reactivity are reported in (d) (Galanti et al, 2021). (F) Mechanism of the chemical "translation" carried out by protocells for murine stem cells.…”
Section: Emergence Of Advanced Biomimetic Behavioursmentioning
confidence: 99%
“…PCMs are centimetre sized assemblies of covalently ligated azide-and strained alkyne-functionalised protocells that are robust, free standing, stable in water, and capable of chemical communication (Figure 2E). (Galanti et al, 2021) Most importantly, PCMs can be easily manipulated by hand making them ideal candidates for a variety of different applications from materials science to regenerative medicine.…”
Section: Interconnected Protocell Networkmentioning
confidence: 99%